2006
DOI: 10.1136/oem.2005.025866
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic noise and hypertension

Abstract: Background: It has been suggested that noise exposure increases the risk of hypertension. Road traffic is the dominant source of community noise exposure. Objective: To study the association between exposure to residential road traffic noise and hypertension in an urban municipality. Methods: The study population comprised randomly selected subjects aged 19-80 years. A postal questionnaire provided information on individual characteristics, including diagnosis of hypertension. The response rate was 77%, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
89
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(97 citation statements)
references
References 16 publications
3
89
1
1
Order By: Relevance
“…Contrary to many other studies [12][13][14][35][36][37], noise did not show any significant association with any cardiovascular or respiratory disease. Road traffic noise was transferred to the number of potentially affected residents per building block, and scaled in percent per borough.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to many other studies [12][13][14][35][36][37], noise did not show any significant association with any cardiovascular or respiratory disease. Road traffic noise was transferred to the number of potentially affected residents per building block, and scaled in percent per borough.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, besides genetic disposition, family history, and previous atopic disease [49,50], individual behavioral factors such as smoking status including passive smoking, alcohol intake, or physical activity, awareness for diseases such as hypertension and factors describing the daily routine are discussed to be associated with the occurrence of different cardiovascular and respiratory health outcomes [7,23,[35][36][37][51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…People who have survived chronic lifethreatening illnesses are often confronted with multiple physical and psychological stressors: unemployment, homelessness, poverty, noise, overcrowding, reduced social support and deteriorating mental status, among others (1)(2)(3). These factors can disrupt people's ability to access and implement medical care, predisposing patients to engage in risky health behaviours, miss appointments and adhere poorly to treatment plans (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…It has therefore been hypothesized that exposure to transportation and occupational noise may cause permanent vascular effects (10). Epidemiological studies have shown contradicting results, but -taken together -the evidence suggests an increased risk of hypertension associated with exposure to road-traffic, aircraft, or occupational noise (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In a review of residential-traffic noise exposure and hypertension, the meta-analysis showed an odds ratio (OR) of 1.034 [95% confidence interval (95% CI) 1.011-1.056] per 5 dBA increase of the 16-hour average road-traffic noise level (L Aeq,16h ) range 45-75 dBA (20).…”
mentioning
confidence: 99%